Minimum important difference of shuttle walk tests in patients with interstitial lung disease following pulmonary rehabilitation - Jakub Zatloukal; Linzy Houchen-Wolloff; Sarah Ward; Fasihul Khan; Sally J. Singh (ERJ Open Research)
Background Pulmonary rehabilitation (PR) is recommended for patients with interstitial lung disease (ILD). The impact of PR on exercise capacity, symptom management and mortality risk in ILD is well established; however, there are limited studies reporting on the minimal important difference (MID) for shuttle walk tests (SWTs) in the ILD population. The aim of this study was to establish the MID for both the incremental and endurance shuttle walking tests (ISWT/ESWT) in the ILD population and to evaluate the association with survival. Participants The study includes 207 participants with ILD (mean±sd age 71.1±9.5 years, forced vital capacity 2.32±0.79 L) who completed PR. Results The baseline ISWT was 251.4±153.3 m and ESWT was 217.7±136.3 s. There were significant improvements for both the ISWT and ESWT following the PR programme (44.5±77.0 m (p<0.001) and 312.3±338.6 s (p<0.001)). MID was calculated through a combination of distribution (0.5×sd) and anchor-based techniques (global rating of change (GROC) and receiver operating characteristic (ROC) analysis). The distribution-based technique yielded an MID of 38.5 m for ISWT and 169.3 s for ESWT. ROC analyses yielded an MID of 35 m for ISWT and 200 s for ESWT; and the GROC yielded an MID of 58.5 m for ISWT and 209.0 s for ESWT. Survival analysis showed that improvements in exercise tolerance are associated with improved survival. Conclusion Our data suggest an MID of 35.0–38.5 m for ISWT and 170–209 s for ESWT for patients with ILD. The size of improvements in SWT is associated with a survival advantage in ILD individuals who attend and complete PR.